Determinant Analysis of Employee’s Interest in Making Personal Financial Planning - Muhammad Rizal Bakri; Dina Diana (Universitas Darussalam Gontor, 2024)
Personal financial planning needs to be done by an employee. However, in practice there are several problems that hinder this such as: the low level of financial knowledge in Indonesian society, the lack of financial discipline, and the large number of consumption levels that exceed the limit. This study aims to analyze the factors that influence employee interest in making personal financial planning. The financial attitude, social influence, and financial self-efficacy variables will act as independent variables that will affect the dependent variable, namely personal financial planning. This research was conducted in the Bekasi area by taking a sample of 172 respondents. The sampling method used purposive sampling and analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). The result is that the financial attitude and financial self-efficacy variables have a positive and significant effect on personal financial planning and the social influence variable has no effect on personal financial planning.